Projeto de um dispositivo para o controle de amortecedores magneto-reológicos usando recursos da lógica nebulosa - Silva, Rodrigo do Nascimento e (2014)
In this work we proposed and developed a system of control vehicular suspension, semi active, using a magneto rheological damper (MR). For the numerical simulations were considered: a model non-linear an complete car, a fuzzy control system to determine strength of the damper and a system for determining the electrical current applied the damper. The results of numerical simulations demonstrated that proposed control strategy improves the safety by the vehicle reducing the shifts the axles the wheels in approximately 7% and the time of exposure of the chassis the vibrations caused by disturbances in the road in approximately 422.56%. In order of implement in the future a proposed control on a MR damper, a prototype of the real control was developed through the use microprocessor system using microcontrollers Arduino Nano V3. For represented the damper, was used - an electrical coil, which has real characteristics near the end cushioning system. The experimental results demonstrated that the prototype developed, faithfully reproduces the numerical results presented preliminarily with reduced error band.